2013
DOI: 10.1155/2013/827248
|View full text |Cite
|
Sign up to set email alerts
|

Skin Ageing: Natural Weapons and Strategies

Abstract: The fact that the skin is the most visible organ makes us aware of the ageing process every minute. The use of plant extracts and herbs has its origins in ancient times. Chronological and photo-ageing can be easily distinguished clinically, but they share important molecular features. We tried to gather the most interesting evidence based on facts about plants and plant extracts used in antiaging products. Our main idea was to emphasize action mechanisms of these plant/herbal products, that is, their “strategi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
104
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(106 citation statements)
references
References 80 publications
1
104
0
1
Order By: Relevance
“…The study showed that white tea extract reduced the activities of the enzymes, which breakdown elastin and collagen and improve skin's natural elasticity and strength [45].…”
Section: Prevent Degradation Of Collagen/elastin and Improve Skin Firmentioning
confidence: 99%
“…The study showed that white tea extract reduced the activities of the enzymes, which breakdown elastin and collagen and improve skin's natural elasticity and strength [45].…”
Section: Prevent Degradation Of Collagen/elastin and Improve Skin Firmentioning
confidence: 99%
“…Phenolic compounds are composed of an aromatic ring that is linked to a hydroxyl group, which donates electrons and hydrogen atoms. As a result, these compounds are exceptional antioxidants (Silva et al, 2010;Binic et al, 2013;Reuter, Merfort, Schempp, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…These factors produce a large number of aggressive oxidants that damage all of the biological skin cell membranes (Silva et al, 2010;Binic et al, 2013;Datta et al, 2011;Dupont, Gomez, Bilodeau, 2013). Accordingly, the use of skin care products and cosmetics has been utilized to mitigate the cutaneous photoaging process (Visscher, Pan, Kitzmiller, 2013) and these products are commonly composed of plant extracts (Binic et al, 2013).A great number of plants and plant extracts are studied for their antioxidative action arising from their phenolic substructures. Phenolic compounds are composed of an aromatic ring that is linked to a hydroxyl group, which donates electrons and hydrogen atoms.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…4 The antioxidants intake was correlated with an improvement of the antioxidant markers level in biological fluids, 5 but the physiological relevance of the antioxidant consumption was not sufficiently demonstrated, according to European Food Safety Agency 6 and United States Department of Agriculture (USDA). 7 Numerous cosmetic products, 8 food additives, 9 herbal health products 10 or nutritional supplements 11 are marketed and commercialized based on their antioxidant content. New substances with higher antioxidant capacity are synthesized from natural compounds.…”
Section: Introductionmentioning
confidence: 99%